Accelerating orthodontic tooth movement with the aid of periodontal surgery - the practitioner viewpoint - Kim Berna; Dreyer Craig W.; Sampson Wayne (Sciendo, 2014)
Introduction: There has been a revival of interest in the acceleration of orthodontic tooth movement (OTM) by inducing injury to dentoalveolar cortical bone. Termed corticotomy, the procedure offers an advantage to adult patients whose bone metabolism is such that any reduction in treatment time would be welcomed. The procedure has been refined for over 100 years and recent research indicates treatment duration may be reduced often by as much as a third, but it is not clear how widely the method is applied in practice. For the procedure to be successful, careful interdisciplinary management by orthodontists and periodontists is required. However, information regarding the attitude and knowledge of practitioners and the frequency of the procedure performed in Australia and New Zealand is lacking.